Quest for a reference standard for viscosity at high temperatures and high pressures - Avelino, Helena Maria da Nóbrega Teixeira (2018)
This communication is dedicated to give notice of the present situation concerning the proposal of tris(2-ethylhexyl) trimellitate (TOTM) to be a reference standard fluid for viscosity at high temperatures and high pressures. This proposal stems from an internal project of the International Association for Transport Properties (IATP). A general overview of the efforts carried out so far by the scientific community towards that objective will be made. This will be complemented by a description of its main characteristics that support its proposal. In particular, the present work is concerned with the determination of the shear dependence of the viscosity of TOTM. Moreover, new results for the density of TOTM at moderately high temperatures and pressures up to 70 MPa are presented.